2009
DOI: 10.2165/11530430-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with Pheochromocytoma in a Single Centre Over 16 Years

Abstract: These data from a large cohort of patients are consistent with those reported in the literature and show that pheochromocytoma is an in important challenge for clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 41 publications
1
28
0
2
Order By: Relevance
“…According to literature data [ 20 , 31 33 ], LA is indicated in patients affected by PCC up to 8 cm, incidentalomas up to 6 cm and metastases <6 cm. Thanks to the use of ultrasound or radiofrequency dissection, we also demonstrated that minimal invasive approach can be safely performed by experienced surgeons also in the treatment of benign tumors larger than 6 cm and in case of metastases, extending the previous surgical indications [ 5 , 6 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to literature data [ 20 , 31 33 ], LA is indicated in patients affected by PCC up to 8 cm, incidentalomas up to 6 cm and metastases <6 cm. Thanks to the use of ultrasound or radiofrequency dissection, we also demonstrated that minimal invasive approach can be safely performed by experienced surgeons also in the treatment of benign tumors larger than 6 cm and in case of metastases, extending the previous surgical indications [ 5 , 6 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension, either paroxysmal or sustained, is the most consistent finding in neoplasms, and the classical triad of symptoms (headache, palpitations, and diaphoresis) is present in more than 50% of patients. 2 In severe cases, a patient can present with myocardial infarction, heart failure, pulmonary oedema, arrhythmias, or intrachranial hemorrhage. The coexistence of PHEO and Parkinson's disease or Parkinsonism is very rare, with only 3 cases reported in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Various phenotypical presentation depends on various productions of catecholamine metabolites, such as 3methoxytyramine, normetanephrine and metanephrine, and eventually a mixed combinations of their secretion [1]. Conversely, about 1% of catecholamine-secreting tumors result asymptomatic, representing an incidental finding [2].…”
Section: Discussionmentioning
confidence: 99%